REHOUSING, AS MECHANISM FOR URBAN RENEWAL AND ELIMINATING PRECARIOUS HOUSING IN TISSEMSILT CITY (WESTERN ALGERIA) - Faradji Khalid,; Meziani Aicha,; Belgrana Rachida, (International Journal of Innovative Technologies in Social Science, 2024)
The city of Tissemsilt (formerly Vialar), one of the colonial urban centers built in the agricultural areas of Western Algeria, has witnessed significant demographic and urban growth due to its location and its natural and agricultural potential, which qualified it to play a role in attracting people and jobs, especially after its administrative promotion to wilayat status in 1984. This has affected its urban landscape due to the growth of its housing stock, which is deteriorating due to its age and fragility, especially the old ones and those that were illegally built at the end of the 1970s and 1980s on public lands. that are uninhabitable, i.e. candidates for demolition because they cannot be rehabilitated in order to raise their level of well-being regardless of their legal nature, represent more than a quarter of its total housing stock (3324 dwellings spread over 28 sites), according to a census carried out by the Ministry of Housing and Urbanization in 2007.This article aims to study the current situation of precarious housing more than 17 years after its census, especially in the city center, and to study the spatial and social implications of the urban renewal process adopted by the state to improve the face of the city of Tissemselt and upgrade its urban environment through rehousing and the recovery and reconstruction of real estate, and to achieve this end we used theoretical and quantitative approaches to analyze the policy of eliminating precarious housing that raised much controversy since its adoption. To achieve this goal, we used theoretical and quantitative approaches to analyze the policy of eliminating precarious housing, which has raised a lot of controversy since its adoption.